Perlakuan Panas Kering dan Ekstrak Rimpang Lengkuas terhadap Benih Kedelai Terinfeksi Xanthomonas axonopodis: Dry Heat Treatment and Galangal Rhizome Extract on Soybean Seeds Infected with Xanthomonas axonopodis - Ramdan, Evan Purnama; Risnawati, Risnawati; Yulianti, Fitri (Jurnal Fitopatologi Indonesia, 2024)
Dry Heat Treatment and Galangal Rhizome Extract on Soybean Seeds Infected with Xanthomonas axonopodisSoybean (Glycine max) is one of the sources of vegetable protein whose demand continues to increase. One of the main obstacles in soybean cultivation is the bacterial pustule seed-borne disease caused by Xanthomonas axonopodis pv. glycine. This study aimed to evaluate dry heat treatment and galangal rhizome extract on the suppression of X. axonopodis pv. glycine population and vigor of soybean seeds infected with the bacteria. The study was arranged in a completely randomized design. The first experiment was dry heat treatment at 45 ℃ with heating times of 6, 12, and 24 hours, and control without heating. The second experiment was soaking the seeds for one hour in galangal rhizome extract with concentrations of 25%, 20%, and 15%, and the control (water). The variables observed were bacterial population, germination, vigor, and viability of the seeds. The results showed that heat treatment and galangal rhizome extract had a significant effect on reducing the population of X. axonopodis carried by soybean seeds. Treatment of soybean seeds with dry heat for 24 hours caused the seeds to be free of X. axonopodis, but seed germination and vigor decreased. While seed treatment with 25% galangal rhizome extract caused the X. axonopodis population to decrease to 7.0 × 102 cfu mL-1, while not affecting soybean vigor and viability. The results indicate that dry heat treatment has better potential than galangal rhizome extract in eliminating X. axonopodis in soybean seeds. However, because heat treatment has a negative impact on seed germination, it is necessary to find the optimal heating temperature and time to suppress X. axonopodis populations without reducing seed viability.